The impact of a calming supplement on performance in the equine athlete - Williams, J.; Green, M. (DCA Report; Nr. 044, 2014)
The difference between winning and losing in sport can sometimes be attributed to the psychological status of athletes. In equestrianism, a horse`s temperament is often cited by riders as key to successful performance and horses that have trouble relaxing can be problematic. Magnesium and calcium based supplements or `calmers` are available, which claim to enhance performance by reducing a horse`s nervousness. However, there is a lack of qualitative or quantitative evaluation of their efficacy. This study investigated the impact on performance of feeding a calmer in experienced equestrian partnerships. Five warm-blood combinations were selected, 1.30 m + show-jumping n=2, 3* eventing n=2, advanced dressage n=1, comprising 3 geldings and 2 mares. Horses had never used a calmer and all riders were experienced, mean 7.8±2.8 years. Riders completed a questionnaire rating temperament and `rideability`, using likert scales, at home, during competition warm-up and at events prior to feeding a chelated calcium calmer `Cool, Calm & Collected®` as per manufacturer`s instructions. A training diary was kept during the trial, questionnaires were repeated after 6 weeks and competition results were reviewed. Wilcoxon signed rank tests evaluated if differences existed in temperament and rideability ratings pre and post calmer administration. The variables aggression, irritability, dominance, quickness to learn and tries hard did not differ throughout the trial (P>0.05). A number of temperament descriptors were rated as significantly improved at home, during competition warm-up and the event: skittish (P<0.003), excitable (P<0.0008), tense (P<0.003) and panics easily (P<0.003). Rideability improved across all scenarios (P<0.0006); partnerships recorded significant improvement in competition results (P=0.003). Qualitatively riders consistently commented that horses were more relaxed, less argumentative, more focused and exhibited enhanced performance levels when fed the calmer. It appears that the use of a calmer even in experienced partnerships has resulted in improved performance attributed by riders to changes in the psychological profile of their equine partners and evidenced by improved competition results. However, it is difficult to ascertain if a placebo effect occurred within the riders which could have also influenced performance. Further work using larger populations and placebos across experience and competitive levels. LP: A horse`s temperament can impact upon competitive performance. Calming supplements are often used to improve equine performance, yet there is limited evidence of the effectiveness of calming supplements. In five experienced combinations, competition results and rideability of horses improved with the use of a calmer but more work is needed to substantiate these results.